The Effect of Interactivity and Trust on Purchase Intention: The Moderating Role of Time Pressure in Live Streaming Commerce - Putri Tristiana, Salsabila; Arifin, Zainul; Sunarti, Sunarti (FIA UB, 2026)
This study examines the influence of interactivity on purchase intention in live-streaming commerce on Shopee Live for fashion products. The study also considers trust as a mediating variable, while time pressure is a moderating factor that may alter the relationship between trust and purchase intention. The research applies a quantitative explanatory approach. Data were collected from 220 undergraduate students who had previously watched and interacted in Shopee Live. The data were analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM). The results show that higher interactivity during live-streaming commerce is associated with stronger purchase intention and greater consumer trust. When viewers can interact directly with the seller, they tend to feel more confident about the information provided. This trust then positively influences their purchase intention and partially explains how interactivity influences it. At the same time, stronger time pressure weakens the effect of trust on purchase intention. It means that when urgency is too strong, consumers may rely less on trust and focus more on making quick purchase decisions.